2009
DOI: 10.3164/jcbn.08-252
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Biomarkers and Lifestyles in Japanese Healthy People

Abstract: SummaryThe urinary concentrations of 8-isoprostane and 8-hydroxy-2'-deoxyguanosine (8-OHdG), which are biomarkers of oxidative stress, were measured in 677 Japanese people without any diseases, and their correlations with lifestyle facotrs, lifestyle-related blood biochemical parameters, and dietary intake of antioxidative vitamins were investigated. The mean urinary concentration of 8-isoprostane and 8-OHdG was 0.58 ng/mg creatinine and 8.43 ng/mg creatinine, respectively. Mean urinary 8-isoprostane was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
109
6
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 46 publications
11
109
6
3
Order By: Relevance
“…Many studies have found a negative correlation between urinary 8-OHdG excretion and BMI. [17][18][19] However, we did not find such an association in our study, possibly because of the wide distribution of urinary 8-OHdG levels or our small sample size. Systemic oxidative DNA damage was greater in morbidly obese patients, but this increase was not related to weight gain and was more evident in serum than urine samples.…”
Section: Discussioncontrasting
confidence: 51%
“…Many studies have found a negative correlation between urinary 8-OHdG excretion and BMI. [17][18][19] However, we did not find such an association in our study, possibly because of the wide distribution of urinary 8-OHdG levels or our small sample size. Systemic oxidative DNA damage was greater in morbidly obese patients, but this increase was not related to weight gain and was more evident in serum than urine samples.…”
Section: Discussioncontrasting
confidence: 51%
“…Overall, shortened LTL mirrors the cell's mitotic history and replicative history of hematopoietic stem cells, and is further subjected to the effects of inflammation and oxidation (36,37,64). Interestingly, as prior reports show, there are gender-specific effects of oxidative stress and inflammation markers in response to psychological stress, lifestyle, and disease (33,65,66). Although estrogen was shown to have antioxidant neuroprotective effects in response to stress for females (45,67), young women may be more sensitive to psychological stress (30).…”
Section: Discussionmentioning
confidence: 83%
“…The standard level of urinary 8-OHdG (corrected by the Cre level) employed as a stress marker, as provided by the manufacturer of the measurement kit, is 8.4 ng/mg Cre [16], and that reported as the standard for healthy adults is 15.7 ng/mg Cre [3]. The urinary 8-OHdG in the elderly disaster victims was slightly lower than that in healthy subjects aged 60 years or older [17] and higher than that in healthy subjects aged 40 years or older [18].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported a rise in urinary 8-OHdG level with age [10,18,21], other studies found no agerelated difference [19]. In terms of an association between gender and urinary 8-OHdG level, urinary 8-OHdG has been reported to be higher in males than in females [9,10,14], but the gender difference was resolved after correction by the creatinine level [3].…”
Section: Discussionmentioning
confidence: 99%